The IMPLEMENTASI KURIKULUM MERDEKA DALAM PROSES PEMBELAJARAN DI SD NEGERI 67 PERCONTOHAN BANDA ACEH - safira ariani; Intan Safiah; Aida Fitri (LPPM Universitas Cipta Mandiri, 2025)
The implementation of the Merdeka Curriculum is the execution of a curriculum that provides teachers and educational units the freedom to design and carry out flexible learning, focusing on deepening concepts and strengthening student competencies according to the needs and interests of the students. This study aims to describe the implementation of the Merdeka Curriculum in the learning process and to assess teacher performance in supporting the implementation of the Merdeka Curriculum during the learning process. This research uses a qualitative descriptive approach, with data collection techniques including observation, interviews, documentation, and questionnaires. The data analysis methods consist of data reduction, data presentation, and data verification, while the questionnaire uses a Likert scale. Based on the research results, it is known that (1) the implementation of the Merdeka Curriculum in the learning process at SD Negeri 67 Percontohan Banda Aceh has been running well, including in learning planning, learning implementation, and learning evaluation; (2) teacher performance in supporting the implementation of the Merdeka Curriculum in the learning process received a high score, which means that teacher performance is very much in accordance with the rules and provisions of the Merdeka Curriculum.